PENGARUH MODEL PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION BERBANTUAN MODUL IPS TERPADU TERHADAP HASIL BELAJAR IPS SISWA DI SMPN 02 SIKUR TAHUN PELAJARAN 2009/2010 - rohaeniah zein (Educatio, 2010)
The purpose of the reaserch to know â€the influences of cooperative learning model group investigation with IPS module service integrated by the reasult of social learning of the student in junior high 02 Sikur academic year 2009/2010â€ this research was an experimental research. With population of all eighth grade student in SMPN 02 Sikur consisting of three (3) classes. To take sampling doing with a tehnic cluster random sampling. The data collected was analyzed using a formula t-test. Based on the analysis of data obtained of tarithmatic 15,8 and 2,77 ttable value at signivicance level  of 5% with df = 28 + 28 - 2 = 54, it is show of tcount higher then ttable (15,8 2,77) it can be concluded that is an influences of the application of cooperative learning model group investigation (GI) to the learning outcomes of student in junior high IPS integrated 02 Sikur academic year 2009/2010. Keywords: Cooperative Learning Type Group Investigation and Learning